Electro-optical hybrid logic gates - Ekkurthi Sreenivasa Rao; Satyam, M.; Lal Kishore, K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
An Electro-Optical Hybrid Logic Gate is defined as a circuit that accepts
either electrical or optical signals and produces both electrical and optical signals. This
paper explores the feasibility of developing hybrid gates for logic functions namely OR
and AND, which can perform the intended logic function either with electrical or optical
input signals and produce the output both in the form of electrical and optical signals.
These hybrid logic gates are proposed and implemented using phototransistors and
LEDs. The logic circuits are found to be operating satisfactorily for the defined logic
levels